PENERAPAN LATIHAN LITERASI DAN NUMERASI UNTUK MENINGKATKAN KEMAMPUAN BELAJAR - Rianita, S.Pd. M.Pd., Ni Made; Radharani, Sri; Oktapiani, Ni Komang Ayu Tria; Damayanti, Luh Sri; Pujiswari, Made Atmarwati (Penerbit Widina, Widina Media Utama, 2023)
The service team held activities to implement literacy and numeracy training to improve students' learning abilities at SD N 5 Bondalem. This activity is carried out through several stages. First, the team conducted a needs analysis of the students so that the team knew what the students' weaknesses were in implementing literacy and numeracy. The training was carried out for 3 months through the independent campus learning program through training activities outside of class hours through pre-tests and post-tests. After the activity ended, students were evaluated on the extent of their literacy and numeracy results. Participants who took part in the activity were students in grades V and VI of SD N 5 Bondalem. The participants consisted of 25 male students and 28 female students. Through the implementation of this literacy and numeracy training, the results showed that there was an increase in students' learning abilities at SD N 5 Bondalem. ABSTRAKTim pengabdian mengadakan kegiatan Penerapan Latihan Literasi dan Numerasi Untuk Meningkatkan Kemampuan Belajar Siswa SD N 5 Bondalem. Kegiatan ini dilaksanakan melalui beberapa tahapan. Pertama, tim melakukan analisis kebutuhan terhadap siswa sehingga tim mengetahui apa yang menjadi kelemahan siswa dalam penerapan litearasi dan numerasi. Pelatihan dilaksanakan selama 3 bulan melalui program kampus merdeka-merdeka belajar melalui kegiatan latihan di luar jam pelajaran melalui pre-test dan post-test. Setelah kegiatan berakhir, siswa dievaluasi sejauh mana hasil literasi dan numerasinya Peserta yang mengikuti kegiatan adalah siswa kelas V dan VI SD N 5 Bondalem. Peserta yang mengikuti terdiri dari 25 siswa laki-laki dan 28 siswa perempuan. Melalui penerapan latihan literasi dan numerasi ini, didapatkan hasil bahwa terjadi peningkatkan kemampuan belajar siswa di SD N 5 Bondalem.